Fabrication of silicon nanowire sensors for highly sensitive pH and DNA hybridization detection - Abd Rahman, Siti Fatimah; Yusof, Nor Azah; Md Arshad, Mohd Khairuddin; Hashim, Uda; Md Nor, Mohammad Nuzaihan; Hamidon, Mohd Nizar (Multidisciplinary Digital Publishing Institute, 2022)
A highly sensitive silicon nanowire (SiNW)-based sensor device was developed using electron beam lithography integrated with complementary metal oxide semiconductor (CMOS) technology. The top-down fabrication approach enables the rapid fabrication of device miniaturization with uniform and strictly controlled geometric and surface properties. This study demonstrates that SiNW devices are well-aligned with different widths and numbers for pH sensing. The device consists of a single nanowire with 60 nm width, exhibiting an ideal pH responsivity (18.26 × 106 Ω/pH), with a good linear relation between the electrical response and a pH level range of 4–10. The optimized SiNW device is employed to detect specific single-stranded deoxyribonucleic acid (ssDNA) molecules. To use the sensing area, the sensor surface was chemically modified using (3-aminopropyl) triethoxysilane and glutaraldehyde, yielding covalently linked nanowire ssDNA adducts. Detection of hybridized DNA works by detecting the changes in the electrical current of the ssDNA-functionalized SiNW sensor, interacting with the targeted ssDNA in a label-free way. The developed biosensor shows selectivity for the complementary target ssDNA with linear detection ranging from 1.0 × 10−12 M to 1.0 × 10−7 M and an attained detection limit of 4.131 × 10−13 M. This indicates that the use of SiNW devices is a promising approach for the applications of ion detection and biomolecules sensing and could serve as a novel biosensor for future biomedical diagnosis.